Citral stabilization and characterization of nanoemulsions stabilized by a mixture of gelatin and Tween 20 in an acidic system. (2nd February 2017) - Tian, Huaixiang; Li, Danfeng; Xu, Ting; Hu, Jing; Rong, Yuzhi; Zhao, Bo
Abstract: BACKGROUND: Citral is one of the most important flavor compounds in fresh juice and lemon oil. Unfortunately, citral is chemically unstable and degrades over time in aqueous solutions. Here, citral nanoemulsions including a mixture of gelatin and Tween 20 as emulsifiers were produced in an effort to maintain the stability of citral in an acidic system. RESULTS: The mean droplet size and polydispersity index of the citral nanoemulsion were 467.83 nm and 0.259 respectively when the mass ratio of gelatin/Tween 20 was 3:1 and the total emulsifier concentration of the emulsion system was 10 g kg −1 . The citral nanoemulsion remained stable during storage for 14 days at 30 °C. Therefore this nanoemulsion system effectively protected citral from degradation and decreased the formation of off‐flavor compounds (e.g. p ‐cymene, p ‐cresol and p ‐methylacetophenone) relative to a single emulsifier. CONCLUSION: The mixture of gelatin and Tween 20 enhanced the stability of citral under acidic conditions and could be used as an effective emulsifier to protect citral from degradation under acidic environments in the food industry. © 2016 Society of Chemical Industry